Anti-Planktonic, Antibiofilm, and Synergistic Effects of Nasturtium officinale and Psidium guajava Hydroethanolic Extracts Against Standard and Clinical Strains of Enterococcus faecalis - de Carvalho, Lara Steffany [UNESP]; da Silva, Livia Ramos Dorta [UNESP]; Carvalho, Cláudio Antonio Talge [UNESP]; Marcucci, Maria Cristina [UNESP]; de Oliveira, Luciane Dias [UNESP]; Abu Hasna, Amjad [UNESP] (MDPI, 2025)
Enterococcus faecalis is strongly associated with secondary/persistent root canal infections, being the most prevalent bacterium in cases of apical periodontitis in previously treated teeth. This study was elaborated to evaluate the anti-planktonic, antibiofilm, and synergistic effects of Nasturtium officinale and Psidium guajava hydroethanolic extracts against standard and clinical strains of E. faecalis. Firstly, the N. officinale extract was prepared from watercress leaves, and P. guajava extract was prepared from guava tree leaf shoots. Then, the content of soluble solids was quantified in both. The minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) values of the isolated N. officinale and P. guajava extracts for each bacterial strain were determined using the broth microdilution method, following the Clinical and Laboratory Standards Institute (CLSI) guideline M7-A9. The MTT assay was used to evaluate the antibiofilm activity, and the fractional bactericidal concentration index (FBCI) was utilized to evaluate the synergistic effect of the N. officinale and P. guajava extracts using the checkerboard technique. Again, the MTT assay was used to evaluate the antibiofilm activity of the combined extracts this time. The data were subjected to statistical analysis using ANOVA and Tukey’s test, with a significance level of p ≤ 0.05. It was found that the soluble solid content of N. officinale was 50 mg/mL, and of P. guajava was 33.5 mg/mL. The MBC value of N. officinale was 12.5 mg/mL, and of P. guajava was 0.52 mg/mL against all the tested strains of E. faecalis. The combined 0.1 mg/mL N. officinale + 0.1 mg/mL P. guajava, and 0.1 mg/mL N. officinale + 0.5 mg/mL P. guajava hydroethanolic extracts effectively reduced the biofilm formation of the standard and clinical strain 4 of E. faecalis. Therefore, these combined extracts may be considered as endodontic irrigants in future studies.
Keywords: anti-planktonic; antibiofilm; endodontic infection; endodontic irrigants; Enterococcus faecalis; Nasturtium officinale; Psidium guajava